1979
DOI: 10.1111/j.1432-1033.1979.tb12949.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Secondary and Tertiary Structure of Murein

Abstract: X-ray diffraction, density measurements, and stereochemical data were used in order to disclose the architecture of murein, the rigid component of almost all bacterial cell walls. Dry densities of 1.38 -1.39 g/cm3 were observed for Micrococcus luteus and Staphylococcus aureus. The X-ray data for gram-positive (S. uureiis, M . luteus) and gram-negative (Escherichia cofi) strains were almost identical, showing, in addition to some diffuse scattering with broad maxima corresponding to Bragg values of 0.22 and 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…3E). The radius of a C. crescentus cell is r ¼ 0.25 μm and the length of a disaccharide glycan subunit is near 1.03 nm [estimated using crystal structure of α-chitin and NMR measurements of glycan fragments (35)(36)(37)(38)]. Therefore, the processivity required to explain the observed straightening coefficient based solely on this mechanism is 287 AE 18 nm, which is equivalent to 279 AE 17 subunits.…”
Section: Resultsmentioning
confidence: 99%
“…3E). The radius of a C. crescentus cell is r ¼ 0.25 μm and the length of a disaccharide glycan subunit is near 1.03 nm [estimated using crystal structure of α-chitin and NMR measurements of glycan fragments (35)(36)(37)(38)]. Therefore, the processivity required to explain the observed straightening coefficient based solely on this mechanism is 287 AE 18 nm, which is equivalent to 279 AE 17 subunits.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of murein biosynthesis, disaccharide repeating units are attached to each other to produce glycan helices of different lengths, while the arms of the peptide side chains interact with each other to generate long oligopeptide bridges, endowing murein with a high degree of cross-linking. When performing the conformational analysis of oligomuropeptides, we made the central conceptual assumptions that within the murein tertiary structure, glycan strands have a helical conformation, which was determined by previous X-ray diffraction studies (6,21), and that the geometry of the oligopeptide chains is undistorted and resembles that of free oligomers released from murein by muramidase digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Beneath each plane and at right angles to the glycan chains, there was a plane of peptide chains that were crosslinked at considerable distances; the whole structure made a covalently closed sphere joined by glycan chains in one direction and by oligopeptide chains at 90 o to the glycan chains (29,32,36,37,41). This model was discounted by X-ray diffraction data (6,21), which proved that glycan strands do not possess a straight chitin-like conformation but represent right-handed helices with 4 disaccharides units per turn. Although there are no conditions under which helices can be introduced into the proposed type of architecture, the "chitin" model is surprisingly present even in today's microbiology textbooks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual orientation of the glycan chains within the cell wall is uncertain. Early models suggested that the glycan strands were arranged in shell-like, parallel structures around the cell (72,170). A recent model suggests that the glycan and oligopeptide chains are in fact perpendicular to the plasma membrane, with oligopeptide chains adopting a zigzag conformation to connect adjacent glycan strands (72).…”
Section: Understanding Vancomycin Resistance: the Staphylococcal Cellmentioning
confidence: 99%